Judicial Considerations in Isbat Nikah for Unregistered Marriages at Sukoharjo Religious Court: A Study of Religious Court Decision Number 16/Pdt.P/2025/PA.Skh - Mustajabah Khoirun Nisa’ Muna Afifah; Syamsuddin Syamsuddin; Aditya Fajri Kurnia Pradana; Anisah Amin Zaini Syafiuddin (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
This study aims to (1) Examine judges' considerations in deciding marriage confirmation cases in the decisions studied. (2) Analyze marriage confirmation procedures according to statutory regulations and Islamic law. (3) Determine the legal implications of determining marriage confirmation for the parties. This study uses a normative juridical approach with a descriptive-analytical nature to examine the determination of marriage confirmation in Decision Number 16/Pdt.P/2025/PA.Skh. The data used are secondary data obtained through literature studies, including laws and regulations and court decision documents. Data collection was carried out by reviewing legal materials relevant to the research problem. Data analysis techniques were carried out qualitatively by interpreting the legal provisions and facts in the decision. This study aims to provide an understanding of the judge's considerations, procedures, and legal implications of marriage confirmation. The results of the study indicate (1) that judges' considerations are carried out comprehensively, referring to Islamic law and positive law in Indonesia. Judges assess the fulfillment of the pillars and requirements for a valid marriage, ensure the absence of obstacles to the marriage, and consider aspects of public interest, legal certainty, and protection of the rights of the parties. (2) The marriage confirmation procedure begins with submitting an application to the Religious Court, followed by examination through trial and evidence, until a decision is made by the judge if all requirements are met. From an Islamic legal perspective, marriage confirmation is proof of a valid marriage according to religion, while in positive law it is a means of obtaining state recognition through official registration. (3) The legal implications of the marriage confirmation are to provide formal legality to the marriage, guarantee legal certainty, and protect the civil rights of the husband, wife, and children. Thus, marriage confirmation plays an important role in bridging the validity of a marriage according to religious law and recognition according to state law